Determination of Epimedin B in Rat Plasma and Tissue by LC-MS/MS: Application in Pharmacokinetic and Tissue Distribution Studies - Qianru Feng; Shunjun Xu; Jiejing Yu; Shuai Sun; Liu Yang (Journal of Analytical Methods in Chemistry)
A simple, sensitive, and specific liquid chromatography tandem mass-spectrometric method was developed and validated for the determination of epimedin B in rat plasma and tissue samples. After being processed with a protein precipitation method, these samples were separated on an Agilent Eclipse XDB-C18 column with an isocratic mobile phase consisting of acetonitrile and 0.1% formic acid aqueous solution (32 : 68, v/v). The calibration curve of epimedin B was linear over the concentration range from 1 to 500 ng/mL in plasma and tissue homogenate. The method was then applied to pharmacokinetic and tissue distribution studies after a single oral administration of Herba Epimedii extract to SD rats. Results showed that epimedin B reached the plasma peak concentration at 0.4 h and the terminal elimination half-life was 1.6 h in rat plasma, and the plasma area under the curve from time zero to infinity (AUC0–∞) was 14.35 μg/L·h. The concentration distribution of epimedin B in rat tissue was in the following order: liver > ovary > womb > lung > kidney > spleen > heart > brain, indicating that the compound could be widely distributed in rat, and the reproductive system may be the principal target of epimedin B for female rat.